Spread Spectrum Modulation Investigation Using MATLAB Developed Tool On Automotive Dc-Dc Converter - Rajamanickam, Sivanyanam; Andrea, Zuccollo; Subramaniam, Siva Kumar; Abd Ghani, Zamre (World Academy of Research in Science and Engineering, 2020)
Electromagnetic Interference (EMI) classified as emission from a device or a system that interrupt normal operation of the own or neighbor system. Generally, EMI is caused by radiation emitted from an external source. The electromagnetic interference classified into conducted emission and radiated emission. Conducted EMI is pass through transmission lines such as wires and PCB traces whereas radiated EMI is caused by induction. Nowadays, spread spectrum concept widely used in design phase of DC-DC converter as a measure to keep emission within automotive EMC defined standard besides filter techniques and PCB designs. In principle, there are many different test measurement setup used in spread spectrum modulation concept for conducted EMI analysis which cause beginners difficult to master the topic. This paper describes a developed MATLAB program for spread spectrum modulation (SSM) techniques with several modulation parameters, profiles, including test measurement setups in EMI analysis.